Case Comparison of Major Digital Business Platforms : Amazon, AliExpress and eBay (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technology has made rapid developments in different sectors of the economy. Commerce is notan exception. The research seeks to establish Amazon, AliExpress, and eBay’s strategies,developments, and specific competitive advantages in the e-commerce industry. The researchfocuses on the financial, supply chain management, payment methods, and publicities sectors.The study uses a mixed-method approach in analyzing the three corporations as markets andmarketplaces. Further, it employs quantitative time series analysis to examine the corporations’internal and external markets. The study utilized disruption theory as its theoretical frameworkand the adoption commitment curve model as its conceptual framework. The research concludesthat the three digital businesses have thrived because of various payment methods, programmatictargeting in publicity, utilization of technology in the supply chain, and enhancing customer trustand loyalty.